Industry versus environment: styles of development and change in a tribal region - the case of Rourkela - Meher, Rajkishor (1997)
The impact of industrialisation on environment, basic amenities, health including pollution-related deseases and other aspects of `Quality of life' have been discussed in this presentation of a case history of Rourkela. - Reproduced
Keywords: Environment; Industrialization